10.36873/jht.v15i2.2162 PP. 70-79 : Wahyudi Wahyudi1 , Andy R. Mojiol2 , Reni Rahmawati1 , Nursiah1 , Patricia E.Putir1: TINGKAT KERUSAKAN TEGAKAN TINGGAL PADA AREAL BEKAS TEBANGAN DI IUPHHK-HA PT GUNUNG MERANTI, PROVINSI KALIMANTAN TENGAH (Residual Trees Damage Rate at Logged Over Forest in Forest Concession of PT.Gunung Meranti, Central Kalimantan Province) - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2020)
Timber harvesting activities in forest concession using the Indonesia Selective Cutting and Planting silvicultural (ISCP) system can cause damage to residual trees. The greater the damage of residual trees to be indicator the less effective the activity. This study aims to determine the damage of residual trees caused by harvesting in the logged-over areas using the ISCP silvicultural system. The study used a research plot measuring 40 m x 240 m (0.96 ha) with 5 replications. Each research plot was consisted of 24 sub plots each for the trees, pole, sapling and seedling levels. Sample felled trees were determined as many as 30 trees. The results showed that the average damage caused by harvesting of 1 tree was 6.46 seedlings/ha; 7.17 saplings/ha; 2.13 poles/ha and 2.25 trees/ha. In general, the damage to residual trees due to felling was 11.28% for seedlings; 11.56% for saplings, 12.14% for poles and 11.8% for trees. The level of damage to seedlings, saplings and poles were in the medium category, while the level of damage to the tree level was in the low category. Keywords: Damage, harvesting, residual trees, silvicultural system